Effect of Ridging and Tie-Ridging Time on Yield and Yield Component of Sorghum in Northern Ethiopia - Worku, Yalelet Abie (International Journal on Food, Agriculture and Natural Resources, 2025)
Abstract                    Water deficit and poor fertility of soil are among the main constraints for sorghum production in northern Ethiopia's semi-arid regions. A field experiment was carried out at Lasta and Sekota districts of the Eastern Amhara Region in Ethiopia to evaluate the effects of Ridging and tie-ridging time on the yield performance of sorghum (Sorghum bicolor). The experiment consisted of eight treatments of ridging time & time of tie (Tie-ridging at planting, Ridge at planting tying 2 Weeks After Planting, Ridge at planting tying 4 Weeks After Planting, Tie-ridging 3 Weeks After Planting, Ridging 2 Weeks After planting & tying 4 Weeks After Planting, Ridge 3 Weeks After Planting & tying 6 Weeks After Planting, Tie-ridging 6 Weeks After Planting); including Shilshalo as a control farmer practice which was arranged in a randomized complete block design (RCBD) with three replication. The experiment revealed that ridging and tie-ridging time has a significant effect on the yield of sorghum. Based on the result,- ridging at planting increased the yield of sorghum by about 37.9 % at Sekota (Aybira) relative to the control (farmer practice), and Tie ridging 3 weeks after planting increased sorghum yield by 30.11% at Lalibela as compared to the control (farmers practice). The highest yield of 3.642 tons/ha and 1.903 tons/ha was obtained from tie ridge at planting for Sekota (Aybira) and tie ridging 3 weeks after planting at Lalibela. Therefore, tie and ridge at planting could be appropriate for sorghum production at Sekota (Aybira) and sorghum growing areas. However, tie-ridge 3 weeks after planting could be appropriate for sorghum production at Lalibela (Kechinabeba) and growing areas.Keywords: - Sorghum, Tie ridge,  water deficit and yield